2007
DOI: 10.1111/j.1365-246x.2007.03455.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper-crustal structure beneath the Strait of Georgia, Southwest British Columbia

Abstract: S U M M A R YWe present a new three-dimensional (3-D) P-wave velocity model for the upper-crustal structure beneath the Strait of Georgia, southwestern British Columbia based on non-linear tomographic inversion of wide-angle seismic refraction data. Our study, part of the Georgia Basin Geohazards Initiative (GBGI) is primarily aimed at mapping the depth of the Cenozoic sedimentary basin and delineating the near-surface crustal faults associated with recent seismic activities (e.g. M = 4.6 in 1997 and M = 5.0 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The updated 3D physical-structure model can be further improved by: (1) incorporation of the 600 m gridded V P model of Dash et al (2007; only the 800 m surface was used here), (2) validation by comparison with future empirical earthquake recordings, and (3) increasing the maximum depth to ∼80 km for simulation of JdF plate earthquakes (constrained to maximum depth of 55 km here). Conclusions are limited to the simulations conducted here and are specific to the chosen epicenter locations and earthquake rupture style.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The updated 3D physical-structure model can be further improved by: (1) incorporation of the 600 m gridded V P model of Dash et al (2007; only the 800 m surface was used here), (2) validation by comparison with future empirical earthquake recordings, and (3) increasing the maximum depth to ∼80 km for simulation of JdF plate earthquakes (constrained to maximum depth of 55 km here). Conclusions are limited to the simulations conducted here and are specific to the chosen epicenter locations and earthquake rupture style.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies in this region have shown that basement units surrounding the Late Cretaceous Georgia basin sediments correspond to V P of ∼5:5-6:0 km=s in the upper 2 km and ∼6:4-6:75 km=s at deeper depths ( White and Clowes, 1984;Zelt et al, 2001;Ramachandran et al, 2004Ramachandran et al, , 2006Dash et al, 2007). Expected reduction in seismic velocity of basement rock units in southwest British Columbia likely occurs in the upper tens of meters, which is not resolved by the chosen 250 m gridded velocity model.…”
Section: Physical-structure Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…The Georgia sedimentary basin in southwest British Columbia is one of a series of basins extending from California to southern Alaska along the Pacific margin of North America (England and Bustin, 1998) and is relatively shallow and wide (130 by 70 km wide by 5 km in depth) compared to basins further south in Seattle, WA (75 by 30 km wide by 8 km in depth; Frankel et al, 2007) and Los Angeles, CA (50 by 30 km wide by 5 km in depth; Magistrale et al, 1996). Properties of the Late Cretaceous and Tertiary sedimentary rocks within the Georgia basin and its basement are known from seismic surveys (White and Clowes, 1984), particularly seismic tomography results of the 1998 Seismic Hazards Investigations in Puget Sound experiment (Brocher et al, 2001; Dash et al, 2007; Ramachandran et al, 2004a). The presence of the Georgia basin is expected to cause amplification of ground motions in Metro Vancouver, based on amplification observed in areas with sediment-filled basins (Campillo et al, 1989; Frankel et al, 2009; Olsen, 2000).…”
Section: Georgia Sedimentary Basinmentioning
confidence: 99%